2011
DOI: 10.1007/s00330-011-2151-1
|View full text |Cite
|
Sign up to set email alerts
|

CT Colonography to exclude colorectal cancer in symptomatic patients

Abstract: CTC has a high sensitivity and negative predictive value in excluding a CRC in patients with colorectal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…‡Than et al 38 included patients with a new colonography diagnosis and identified those with CT colonography in the previous 3 years. 30,31,35,41 not used at all in two (17%) of 12 studies, 39,42 and its use was not reported by one (8%) study. 38 Seven (58%) of 12 studies did not report radiologist experience, four (33%) of 12 studies used radiologists with varying amounts of experience, and in one (8%) of 12 studies 37 the radiologists had previous experience of fewer than 100 cases.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…‡Than et al 38 included patients with a new colonography diagnosis and identified those with CT colonography in the previous 3 years. 30,31,35,41 not used at all in two (17%) of 12 studies, 39,42 and its use was not reported by one (8%) study. 38 Seven (58%) of 12 studies did not report radiologist experience, four (33%) of 12 studies used radiologists with varying amounts of experience, and in one (8%) of 12 studies 37 the radiologists had previous experience of fewer than 100 cases.…”
Section: Resultsmentioning
confidence: 97%
“…Characteristics of included studies 30,31,[33][34][35][36][37][38][39][40][41][42] are shown in table 1. Most were retrospective (nine studies 33,[35][36][37][38][39][40][41][42] ) and done at a single centre (nine studies 33,[35][36][37][38][39][40]42 38 all patients with post-test colorectal cancer were included, rather than only those having CT colonography. The sex and age range of included patients was only reported in seven (58%) of 12 studies; 30,31,35,36,[38][39][40] CT colonography technique was inconsistently reported (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…There is now a significant body of data in the literature, accumulated over the past 15 years, which confirms the value of CTC in diagnosing CRC, both in the screening situation and in symptomatic individuals …”
Section: Discussionmentioning
confidence: 76%
“…There is now a significant body of data in the literature, accumulated over the past 15 years, which confirms the value of CTC in diagnosing CRC, both in the screening situation and in symptomatic individuals. [1][2][3][4][5][6][7] This study, from one institution, has endeavoured to follow similar methodology to the previously published series of NZ studies to determine the accuracy of investigations used for detection of CRC. [7][8][9] Our population comprised mainly (84%) symptomatic patients, while the other studies comprised all symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation